The gyroscope-like economy: hypermobility, structural imbalance and pandemic governance in China. - Xiang, Biao (Inter-Asia Cultural Studies, 2020)
The COVID-19 pandemic urges us to rethink the analytical relations between China, Asia and other parts of the world. Many of what had appeared to be "Chinese characteristics" at the early stage of the outbreak turned out to be common phenomena worldwide. Apparently minor differences, such as the penetration rate of e-commerce, matter a great deal. This essay contributes to this intellectual remapping by proposing two arguments. First, the essay aims to explain the similar governmental reactions in China and other parts of the world—the initial reluctance followed by drastic lockdown—by pointing to the "gyroscope-economy" model that dominates many societies. The economy is structurally imbalanced and has thus become exceedingly dependent on the movements of people, goods and capital, much like a gyroscope, which cannot balance unless spun fast. Second, the essay examines several Chinese-specific characteristics of the gyroscope-like economy, namely the broad-based participation and the high growth rate coupled with low welfare provisions, competitiveness and precariousness. These features are attributable to a combination of hypermobility and authoritarianism. The pandemic may intertwine the two more deeply, in China and beyond.